Association between socioeconomic indicators and pulse wave velocity (PWV) measurements in population studies: a systematic review and meta-analysis - Galatia Photiou; Panayiotis Kouis; Zoi Papasavva; Demosthenes B. Panagiotakos; Nicos Middleton; Andrie G. Panayiotou (BMC Public Health)
Abstract Background Arterial stiffness, which is estimated by pulse wave velocity (PWV), has been associated with cardiovascular morbidity and mortality; however, there is sparse literature on socioeconomic (SES) indicators and PWV. Methods In this systematic review and meta-analysis, evidence was retrieved from cross-sectional and cohort studies on the association of SES indicators (both single and composite) with arterial stiffness. A total of 16,331 records were reviewed and 9 studies included. Results Low educational level was associated with an increase of 0.26 m/s in PWV (95% CI: 0.15 to 0.37; p < 0.001; I2 = 78.2%), whereas low SES was associated with a 0.32 m/s increase of PWV (95%CI: 0.09 to 0.56, p = 0.008, I2 = 93.6%). Conclusion Results underscore the importance of socioeconomic position as a determinant of arterial stiffness. Future studies could benefit from longitudinal designs and more homogeneous SES measures, as well as considering composite indicators of SES like neighborhood/area environment and characteristics, along with individual indicators.